A Platform for Supporting Micro-Collaborations in a Diverse Device Environment - Johnson, David (International Journal of Interactive Mobile Technologies (iJIM), 2009)
Collaborative software is usually thought of as providing audio-video conferencing services, application/desktop sharing, and access to large content repositories. However mobile device usage is characterized by users carrying out short and intermittent tasks sometimes referred to as â??micro-taskingâ??. Micro-collaborations are not well supported by traditional groupware systems and the work in this paper seeks out to address this. Mico is a system that provides a set of application level peer-to-peer services for the ad-hoc formation and facilitation of collaborative groups across a diverse mobile device domain. The system builds on the Java ME bindings of the JXTA P2P protocols, and is designed with an approach to use the lowest common denominators that are required for collaboration between varying degrees of mobile device capability. To demonstrate how our platform facilitates application development, we built an exemplary set of demonstration applications and include code examples here to illustrate the ease and speed afforded when developing collaborative software with Mico.